2022
DOI: 10.1038/s41419-022-04825-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-146a-5p and miR-155-5p promote CXCL12/CXCR7-induced metastasis of colorectal cancer by crosstalk with cancer-associated fibroblasts

Abstract: C-X-C motif chemokine receptor 7 (CXCR7) is a newly discovered atypical chemokine receptor that binds to C-X-C motif chemokine ligand 12 (CXCL12) with higher affinity than CXCR4 and is associated with the metastasis of colorectal cancer (CRC). Cancer-associated fibroblasts (CAFs) have been known to promote tumor progression. However, whether CAFs are involved in CXCR7-mediated metastasis of CRC remains elusive. We found a significant positive correlation between CXCR7 expression and CAF activation markers in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…The results show a substantial decrease in mesenchymal markers along with a decrease in MnSOD level, and conversely, by observing increase in the levels of epithelial markers, it was demonstrated that LEE could regulate both cellular invasion and migration through modulating MnSOD and the EMT process. Thereafter, to confirm the association between CXCR7/4 and the EMT process, we checked the protein expression level under CXCL12 stimulation [ 47 , 48 ]. It was confirmed that treatment with CXCL12 increased the expression of MnSOD along with an increase in CXCR7/4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show a substantial decrease in mesenchymal markers along with a decrease in MnSOD level, and conversely, by observing increase in the levels of epithelial markers, it was demonstrated that LEE could regulate both cellular invasion and migration through modulating MnSOD and the EMT process. Thereafter, to confirm the association between CXCR7/4 and the EMT process, we checked the protein expression level under CXCL12 stimulation [ 47 , 48 ]. It was confirmed that treatment with CXCL12 increased the expression of MnSOD along with an increase in CXCR7/4.…”
Section: Discussionmentioning
confidence: 99%
“…The EMT process is mediated through various transcription factors, inflammatory cytokines, growth factors, and other proteins and enzymes [ 44 ]. It has been also reported that CXCL12 can induce the EMT process through modulating the CXCR4/7 axis to promote cellular invasion and migration [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some differentially expressed RNAs and proteins in exosomes have been identified as potential biomarkers linked to CRC initiation and progression. Wang et al considered that CRC cell-derived exosomal miR-146a-5p and miR-155-5p could activate the JAK2-STAT3/NF- κ B signaling pathways, thereby enhancing the invasive ability of CRC cells [ 33 ]. Studies have found that in human CRC cells, exosomal Nrf2 plays a pivotal role in oxaliplatin resistance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAFs actively contribute to tumor progression by providing physical support to cancer cells (in association with ECM) and releasing several factors, such as VEGF and FGF, that stimulate the angiogenesis [ 29 ]. These cells also play a crucial role during the metastatic processes by the activation of several pathways, including the release of different enzymes able to induce ECM degradation, and then improving cellular migration and invasiveness [ 30 , 31 ]. The ECM is a “cell-derived scaffold” and is a pivotal physical support for all tissues in the human body (except for circulating cells) [ 32 ].…”
Section: Role Of Tumor Microenvironment In Cancer Progressionmentioning
confidence: 99%